VOLUNTEER TEACHER SPIRIT (VOLTS): AMPLIFYING FAMILY AND COMMUNITY ENGAGEMENT IN TEACHER PREPARATION - Francheska Starks, (PUPIL: International Journal of Teaching, Education and Learning, 2025)
Family, school, and community engagement is an important factor in primary school students’ academic performance and social and emotional development. However, there is a lack of attention in teacher preparation curricula focused on supporting and developing preservice and in-service educators’ capacity to engage with their students’ families and communities. As a group of University-based teacher educators, we collaborated with local families and community partners to design an open source, web-based curriculum for teacher educators to provide focused instruction on family, school and community involvement. The online and open format provides accessibility for teacher educators to integrate the content into existing courses or teach them as stand-alone content, and for in-service teachers to access the modules as needed. We use Calabrese Barton and colleagues’ Ecologies of Parental Involvement framework to examine the forms and function of capital accessed and utilized during the collaborative development of the curriculum content.